Evaluasi Implementasi Sistem Digital Pdam Terhadap Kepuasan Pelanggan Pada Pdam Tirta Manakarra Mamuju - Asfirawati; Yislia; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
This study focuses on evaluating the service performance of PDAM Tirta Manakarra through Importance and Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The IPA analysis classifies service attributes into four quadrants based on their importance and performance levels, highlighting areas requiring improvement or retention. Meanwhile, the CSI assessment reveals an overall customer satisfaction score of 58.22%, indicating